Through the Looking Glass: Enhancing Public University Librarians' Entrepreneurial Competencies in Facing the Impact of Globalization (Conceptual Paper) - Siti Nisrin Mohammed Anis; Amran Mohammed Rasli; Noor Hazarina Hashim (International Review of Management and Marketing, 2016)
Human capital and employees' performance are recognized as the premium key resource for organisational competitiveness. However, changes in global finance and organisations are affecting many organisations, including public sectors. Albeit changes, employees across sectors are constantly required to sustain accountability towards  performance. Thus, to survive changes while sustaining competitive advantage, organisations and its employees are recommended to initiate new practices and behaviours. For example, the current financial's condition restricted the public university libraries' abilities to  better serve the community. To accommodate this situation, public universities are recommended to practice self-funding, despite their anticipating role as a public service provider.  This direction creates dilemma to micro units such as the libraries, which existence is solely to serve its community. The libraries are constantly criticised as a cost centre and  being opted to cease service as its functions may be replaceable by other information provider such as Google. Thus, it is important that, the librarians must voluntarily make efforts to re-tool their current competencies and revise their patrons' preferences as well. The efforts are critically needed if the librarians desire to survive the changes and stay relevant.  Thus, this paper postulates a multi-construct antecedents, which consist of entrepreneurial inclinations which may be useful. The overarching theory is based on the Theory of Planned Behaviour and Resource Based View.  This paper reviews literatures associated with the constructs and recommend the advantages of applying it accordingly. It is hopeful that this investigation will contribute additional knowledge on the influence of those constructs towards individuals' work performance as well as adding optional information.